Acid surface treatment of sol-gel derived ZnO thin films for anti-reflection coating application - Khamon, W.; Pecharapa, W. (My University, 2016)
Transparent ZnO films were deposited by sol-gel spin coating process. HCl acid was used in the wet etching process to modify its surface morphology that can be used as an antireflective layer of optoelectric devices. The effect of etching time on its structure, surface morphologies and optical properties were scrutinized. The overall results indicated that HCl acid has obviously effect on significant change in surface morphologies and its roughness varied in the range of 0.5 nm to 4.9 nm.
Keywords: HCl; Surface morphology; Wet etching; ZnO